Empirical Evaluation of the Energy Transition Efficiency in the EU-27 Countries over a Decade—A Non-Obvious Perspective - Jarosław Brodny; Magdalena Tutak; Wieslaw Wes Grebski (Energies)
In response to the escalating challenges of climate change and the urgent need to reduce greenhouse gas emissions, the energy transition has become a central priority of environmental policy worldwide. The European Union (EU), a global leader in implementing sustainable energy solutions, has pursued numerous initiatives aimed at advancing energy transformation. This paper presents the results of an empirical study assessing the efficiency of the energy transition process in the EU-27 countries over the 2013–2023 period. The assessment is based on the dynamic changes in selected indicators relevant to the energy transition, including decarbonization of the energy sector, improvements in energy efficiency, the share of renewable energy sources, energy import dependency, greenhouse gas emissions, and the extent of energy poverty. A multidimensional analysis was conducted using a specially developed energy transition efficiency index, where indicator weights were determined through the Analytic Hierarchy Process. The study also examined two distinct sub-periods (2013–2018 and 2018–2023), as well as a series of shorter, two-year intervals (2013–2015, 2015–2017, 2017–2019, 2019–2021, and 2021–2023), enabling a more nuanced analysis of the temporal evolution of transition efforts. Additionally, principal component analysis was employed to classify the EU-27 countries based on the similarity of their energy transition profiles. The findings reveal significant disparities in the pace and scope of energy transition across member states. Luxembourg, Malta, and the Netherlands demonstrated the most dynamic progress during the study period, followed by Sweden, Denmark, Germany, and Estonia. In contrast, Bulgaria, Hungary, Poland, Latvia, Croatia, and Romania recorded the lowest performance. These differences underscore the varying starting points, policy approaches, and implementation speeds among EU countries in achieving energy transition objectives.